Dominasi Suku Batak pada Lulusan Sarjana di Indonesia: Perspektif Komunikasi Lintas Budaya - Darmawan, Rizki; Rasyid, Abdul (JOM, 2025)
This study aims to analyze the dominance of the Batak ethnic group in bachelor's degree graduation rates in Indonesia through a case study at the Universitas Islam Negeri Sumatera Utara (UINSU), using a cross-cultural communication perspective and social identity theory. This phenomenon raises questions about the communication and cultural factors that support the academic success of Batak students in a multicultural campus environment. The research methodology employs a qualitative-descriptive approach, utilizing literature review and secondary data analysis from the Central Statistics Agency, as well as an examination of intercultural communication based on the theories of Liliweri, Tajfel, and Habermas. The research findings indicate that Batak cultural values such as hagabeon, hamoraon, and hasangapon contribute to strengthening academic motivation, while assertive and open communication styles enable Batak students to excel in building academic relationships and adapting to campus culture. The study also identifies the potential for social exclusion of other ethnic groups if cross-cultural communication is not managed inclusively. These findings offer theoretical contributions regarding the relationship between cross-cultural communication and academic performance, and emphasize the importance of adaptive intercultural communication strategies in creating an equitable academic environment. The recommendations include strengthening cross-cultural communication training programs and facilitating ethnic integration in the campus environment as a form of social reconciliation in higher education.